Meteorological measurements at Auchencorth Moss from 1995 to 2016. (10th December 2018) - Coyle, Mhairi; Cape, John N.; Flechard, Chris; Fowler, David; Helfter, Carole; Jones, Mathew; Kentisbeer, John; Leeson, Sarah R.; Leith, Ian D.; Mullinger, Neil; Nemitz, Eiko; Roberts, Elin; et al.
Abstract: The Auchencorth Moss atmospheric observatory has being measuring meteorological parameters since 1995. The site was originally set‐up to measure the deposition of sulphur dioxide at a site that represented the vegetation and climate typical of NW Europe, in relatively clean background air. It is one of the longest running flux monitoring sites in the region, over semi‐natural vegetation, providing infrastructure and support for many measurement campaigns and continuous monitoring of air pollutants and greenhouse gases. The meteorological sensors that are used, data processing and quality reviewing procedures are described for a set of core measurements up to 2016. These core measurements are essential for the interpretation of the other atmospheric variables. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttp://catalogue.ceda.ac.uk/uuid/8e6cbb111cfd41a19c92aadcb2d040fd . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .